A HAND2 Loss-of-Function Mutation Causes Familial Ventricular Septal Defect and Pulmonary Stenosis. Issue 4 (1st April 2016) - Sun, Yu-Min; Wang, Jun; Qiu, Xing-Biao; Yuan, Fang; Li, Ruo-Gu; Xu, Ying-Jia; Qu, Xin-Kai; Shi, Hong-Yu; Hou, Xu-Min; Huang, Ri-Tai; Xue, Song; Yang, Yi-Qing
Abstract: Congenital heart disease (CHD) is the most common developmental abnormality, and is the leading noninfectious cause of mortality in neonates. Increasing evidence demonstrates that genetic defects play an important role in the pathogenesis of CHD. However, CHD exhibits substantial heterogeneity, and the genetic determinants for CHD remain unknown in the overwhelming majority of cases. In the current study, the coding exons and flanking introns of the HAND2 gene, which encodes a basic helix-loop-helix transcription factor essential for normal cardiovascular development, were sequenced in 192 unrelated patients with CHD, and a novel heterozygous mutation, p.S65I, was identified in a patient with congenital ventricular septal defect (VSD). Genetic analysis of the index patient's pedigree revealed that the mutation was present in all seven affected family members available, but absent in the 13 unaffected family members examined. Besides, in addition to VSD, five of the proband's close relatives also had pulmonary stenosis (PS), and the proband's son also had double outlet right ventricle (DORV). The missense mutation, which altered an evolutionarily conserved amino acid, was absent in 300 unrelated, ethnically matched healthy individuals. Biological analyses using a dual-luciferase reporter assay system showed that the mutant HAND2 was associated with significantly diminished transcriptional activity. Furthermore, the mutation abolished the synergistic activation between HAND2 and GATA4, as well as NKX2.5—two other cardiac core transcriptional factors that have been causally linked to CHD. These findings indicate that HAND2 loss-of-function mutation contributes to human CHD, perhaps via its interaction with GATA4 and NKX2.5.